SChLAP1 contributes to non-small cell lung cancer cell progression and immune evasion through regulating the AUF1/PD-L1 axis - Zhonghai Du; Shuxian Niu; Juan Wang; Jun Wu; Sheng Li; Xiuxiu Yi (Taylor & Francis Group, 2021)
SChLAP1 is recently reported as a key oncogenic long non-coding RNA in human cancer. However, whether SChLAP1 functions in non-small cell lung cancer (NSCLC) and its specific potential regulatory mechanism remain unexplored. In this study, we found that depletion of SChLAP1 significantly inhibited NSCLC cell proliferation, migration and invasion in vitro, and retarded tumour growth and lung metastasis in vivo. SChLAP1 facilitated NSCLC cell immune evasion against CD8+ T cells through PD-1/PD-L1 immune checkpoint. In detail, SChLAP1 was able to directly interact with AUF1, antagonizing the binding between AUF1 and PDL1 mRNA 3'-UTR, resulting in increasing PDL1 mRNA stability and expression, thereby repressing CD8+ T cell function. Consistently, anti-PD-1/PD-L1 treatment evidently blocked the enhanced cell proliferation and invasion caused by SChLAP1 overexpression. Importantly, SChLAP1 was significantly upregulated in NSCLC cell lines, serum and tissues, which was identified as an excellent indicator for the diagnosis and prognosis of NSCLC. In conclusion, our data for the first time uncover that SChLAP1 functions an oncogene in NSCLC by promoting cancer cell immune evasion via regulating the AUF1/PDL1 axis, targeting of SChLAP1 may be a potential approach to improve the efficacy of immunotherapy in NSCLC patients.